Regio- and diastereoselective lipase-catalyzed preparation of acetylated 2-O-glucosylglycerols - D. Colombo; F. Ronchetti; A. Scala; I. Taino; F. Albini; L. Toma (Tetrahedron: Asymmetry, 1994)
2-O-(β-D-Glucopyranosyl)glycerol and 2-O-(2′,3′,4′,6′-tetra-O-acetyl-β-D-glucopyranosyl]glycerol have been submitted to lipase-catalyzed acetylation using Pseudomonas cepacia (LPS) and Candida antarctica (LCA) Upases in organic solvent. The reactions involved the glycerol moiety and were highly diastereoselective: LPS yielded the (2S)-1-O-acetylderivative, while, more interestingly, LCA yielded the (2R)-1-O-acetyl-derivative; in this way the natural compound lilioside A could be obtained. Conversely, lipase-catalyzed hydrolysis of the fully acetylated 1,3-di-O-acetyl-2-O-(2′,3′,4′,6′-tetra-O-acetyl-β-D-glucopyranosyl)glycerol using LCA fiunished the (2S)-1-O-acetyl-derivative showing the same steric preference as the reverse reaction.